Basic radio journalism - Chantler, Paul (Focal Press, 2003)
Basic Radio Journalism is a working manual and practical guide to the tools and techniques necessary to succeed in radio journalism. It will be useful both to students starting a broadcasting career as well as experienced journalists wishing to develop and expand their skills. Based on the popular Local Radio Journalism, this book covers the core skills of news gathering, writing, interviewing, reporting and reading with extensive hints and tips. It outlines working practices in both BBC and commercial radio. There are revamped legal and technical sections as well as a new chapter on the journ.